Monsters of the Waste-land. Materiality and Abjection of Waste - Pezzini, Luca (E|C, 2023)
Waste, as a semiotic object, is intrinsically characterized by materiality. The interplay between matter and form has a key part in a recurring theme in environmental awareness campaigns: namely, the idea of an animal-like form composed by waste material, in a fashion reminiscent of Arcimboldo’s art. I propose a classification scheme “sub specie materiæ” for visuals based on such trope and offer an in-depth analysis of one case study from the 2017 campaign “Turtle, Pelican, Bear” by Fudena. Drawing from Kristeva’s idea of abjection, I show how waste and its representations can be fruitfully understood, on many levels, as “monsters”, detailing how, in this interpretation, a key role is played by materiality and absence (or loss) of form.